A Late Glacial–Early Holocene multiproxy record from the eastern Fram Strait, Polar North Atlantic - Sørensen, Steffen Aagaard; Husum, Katrine; Werner, Kirstin; Spielhagen, Robert f.; Hald, Morten; Marchitto, Thomas (Marine Geology, 2014)
This article is part of Steffen Aagaard Sørensen's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/3007>